PERAN TEKNOLOGI DRONE DALAM MENINGKATKAN PERTAHANAN KEAMANAN LAUT DI INDONESIA - Eka putri, destiana faradiva (LPPM ISTP, 2024)
In recent years, Indonesia, as the largest archipelagic country in the world, has faced various challenges regarding maritime defense security. This research discusses the role of drone technology in enhancing defense security in Indonesia, aiming to analyze the role of drone technology in improving maritime defense security in Indonesia. This study employs a qualitative approach using secondary data that involves data analysis such as documents, reports, and archives. The results of the study indicate that drone technology plays a significant role in improving security and maritime defense in Indonesia. Effective maritime surveillance, rapid response to threats, search and rescue operations, safeguarding maritime infrastructure, and support in military operations are some of the major contributions offered by this technology.